2016
DOI: 10.1186/s40510-016-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molar intrusion with temporary anchorage devices in patients with anterior open bite: a systematic review

Abstract: ObjectiveThe objective of the study is to assess the effect of molar intrusion with temporary anchorage devices on the vertical facial morphology and mandibular rotation during open bite treatment in the permanent dentition.MethodsWe performed a systematic review of the published data in seven electronic databases up to September 2015. We considered studies for inclusion if they were examining the effects of posterior teeth intrusion on the vertical facial morphology with open bite malocclusion in the permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 36 publications
0
45
1
7
Order By: Relevance
“…28 In addition, counterclockwise rotation of the mandible between 2.38 and 3.98 consequent to maxillary and mandibular molar intrusion with TADs was reported. 29 In this particular case, open-bite correction was obtained by a combination of extrusion of the anterior teeth (greater for the mandibular incisors), intrusion of the posterior teeth (greater for the mandibular second molars), and counterclockwise rotation of the mandible, consequent to posterior teeth intrusion (Figures 10 and 11).…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, counterclockwise rotation of the mandible between 2.38 and 3.98 consequent to maxillary and mandibular molar intrusion with TADs was reported. 29 In this particular case, open-bite correction was obtained by a combination of extrusion of the anterior teeth (greater for the mandibular incisors), intrusion of the posterior teeth (greater for the mandibular second molars), and counterclockwise rotation of the mandible, consequent to posterior teeth intrusion (Figures 10 and 11).…”
Section: Discussionmentioning
confidence: 99%
“…3 A vertical facial growth pattern has also been implicated. 4 Although many therapeutic interventions for American Board of Orthodontics have been presented in the literature, 5,6 there seem to be no data describing the three-dimensional (3D) changes in maxilla and mandible caused by the application of these methods during the mixed dentition stage. It is important to intercept deleterious oral habits, and fixed and removable palatal cribs (RPCs) may be used as recall devices in the mixed dentition stage.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to intercept deleterious oral habits, and fixed and removable palatal cribs (RPCs) may be used as recall devices in the mixed dentition stage. [4][5][6] Several studies 4,[7][8][9][10][11][12][13] have been performed to assess the effectiveness of both fixed palatal crib (FPC) and RPC, reporting their posttreatment effects through measurements performed on cephalograms or manually on cast models. Villa and Cisneros 7 observed, in cast models, the dental changes in patients with digital sucking managed with a palatal crib.…”
Section: Introductionmentioning
confidence: 99%
“…These studies confirmed that anchorage for en-masse retraction of maxillary incisors was more effective with TADs than with conventional methods. Another systematic review and meta-analysis assessed the effect of TADs on molar intrusion in patients with open bite and found that out of the 12 acceptable papers 6 reported molar intrusions while the others found no significant effect [18]. Due to the large number of confounders (patients related, user related, product related), the reviews will generally conclude that more quality research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were used by Ciarlantini, who inserted the Aarhus mini-implants in children with agenesis of lateral incisors (Figures 50 and 51). He did, however, combine the advantage of the bone preserving capacity and the fact that the mini-implants with a bracket head could support a temporary replacement of the lateral incisors and allow for the vertical development of the alveolar process [15][16][17][18][19].…”
Section: Figure 49mentioning
confidence: 99%